2016
DOI: 10.1016/j.neuropsychologia.2016.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced working memory performance via transcranial direct current stimulation: The possibility of near and far transfer

Abstract: Although working memory (WM) training programs consistently result in improvement on the trained task, benefit is typically short-lived and extends only to tasks very similar to the trained task (i.e., near transfer). It is possible that pairing repeated performance of a WM task with brain stimulation encourages plasticity in brain networks involved in WM task performance, thereby improving the training benefit. In the current study, transcranial direct current stimulation (tDCS) was paired with performance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 104 publications
(92 reference statements)
1
40
0
Order By: Relevance
“…a lower current intensity of 1 mA can, performance-wise, be superior to stimulation with 2 mA. These data, our own respective findings 4648, 56, 57 , and the more reliable sham control, prompted us to use 1 mA stimulation intensity, despite previous and recent studies showing effects on WM with 2 mA stimulation 28, 29, 34, 58, 59 . However, patients with Parkinson’s disease 60 and schizophrenia 61 seem to benefit more from increased current intensity in regards to cognitive performance.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…a lower current intensity of 1 mA can, performance-wise, be superior to stimulation with 2 mA. These data, our own respective findings 4648, 56, 57 , and the more reliable sham control, prompted us to use 1 mA stimulation intensity, despite previous and recent studies showing effects on WM with 2 mA stimulation 28, 29, 34, 58, 59 . However, patients with Parkinson’s disease 60 and schizophrenia 61 seem to benefit more from increased current intensity in regards to cognitive performance.…”
Section: Discussionmentioning
confidence: 84%
“…Nevertheless, a high variability of stimulation parameters and study settings as well as the complex interaction between task specific neuronal activity and stimulation impede the comparability of the results 30, 31 . Based on this notion, the consideration of asymmetries in the lateral organization of WM 32, 33 might improve the efficacy of tDCS on WM 34 . Imaging and stimulation studies actually suggest a preferential left- and right-sided activation during verbal and spatial WM demands, respectively 3539 .…”
Section: Introductionmentioning
confidence: 99%
“…With respect to clusters in left precentral and middle frontal gyri, the involvement of these areas in motor functions is well established (Petrides, ). The MFG has also been found to be involved in working memory and cognitive control (Abutalebi, ; Abutalebi & Green, ; Aron, ; Osaka, Komori, Morishita, & Osaka, ; Trumbo et al, ) and is part of a broader set of domain‐general regions engaged for cognitively demanding tasks (Duncan & Owen, ; Fedorenko, Duncan, & Kanwisher, ; Novais‐Santos et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…With respect to clusters in left precentral and middle frontal gyri, the involvement of these areas in motor functions is well established (Petrides, 2016). The MFG has also been found to be involved in working memory and cognitive control (Abutalebi, 2008;Abutalebi & Green, 2007;Aron, 2007;Osaka, Komori, Morishita, & Osaka, 2007;Trumbo et al, 2016) , 6, 7, 8, 11, 12, 17, 24, 25, 30, 32, 38, 41, 42, 43, 44 Table). c The method of correction for multiple comparisons (FWE, FDR, Monte-Carlo, or whether there was no correction) is specified in table notes.…”
Section: Language Network For Comprehension and Productionmentioning
confidence: 96%
“…Some findings suggest that performance improvements may be related to current density; studies utilizing a 1mA dose have shown mixed results in an ADHD population [36, 37], whereas a higher dosage (i.e., 2mA compared to 1mA or sham tDCS) has been shown to improve cognitive performance in both healthy samples and neuropsychiatric populations [31, 38, 39]. Furthermore, concurrent performance of a challenging task to engage the targeted control circuits may offer synergistic effects on tDCS-induced neuroplastic changes, promoting greater functional connectivity between large-scale brain networks and improved neural efficiency resulting in improved performance on objective measures of cognitive control [4043]. The fractal N-back is a working memory task which has been shown to robustly activate the DLPFC, and co-administration of this task with tDCS results in greater DLPFC activation than when the task is performed alone [11, 29, 30, 44, 45].…”
Section: Introductionmentioning
confidence: 99%